Epilepsy Care in Nigeria: Factors Influencing Default - Emmanuel Okechukwu Ezunu; Mayowa Owolabi; Adesola Ogunniyi; Uduak Williams (Medsci Publications, 2020)
Introduction: Epilepsy is a common cause of neurologic disability in developing countries where very few patients with the condition have organized regular follow up. This study was conducted to identify factors influencing default of adult epileptic patients in Ibadan. Methodology: This is a prospective study of subjects with epilepsy seen at the out-patient neurology clinic, University College Hospital, Ibadan Nigeria. A total of 147 patients with epilepsy were recruited consecutively. A structured questionnaire for obtaining information on their demographic characteristics, cost of transportation, estimated distance to the clinic, monthly clinic attendance and seizure frequency was initially applied to each patient who was assigned to be seen monthly for the next six months. Those that defaulted from any subsequent visit were identified and the questionnaire was applied to obtain the reason for default from them. Results: Male gender (p=0.0001), estimated distance (p=0.010), cost of transportation (p=0.013) and age below 40 years (p = 0.01) were identified to have influence on clinic default. But gender is the only significant predictors on clinic default at the multivariate analysis level. Conclusions: Creating more advocacy visits on dangers of clinic default, subsidising transportation and decentralising epilepsy care may improve clinic attendance and seizure control.